Poligami Perspektif Filsafat Keadilan Thomas Aquinas - Azmi Wahdani; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss how Thomas Aquinas' philosophy of justice views justice in polygamy. The research method used is a qualitative type through literature study. The results of the discussion of this study are based on Thomas Aquinas' theory, the position of husband and wife is equal and balanced. Thomas Aquinas stated that justice must be based on equality (equality of status, equal rights and obligations, etc.). However, the injustices found in the Marriage Law, firstly, the Marriage Law only provides opportunities for polygamy for husbands, and secondly, the prerequisites for polygamy only focus on women's physical disabilities. There must be a revision of the marriage law to provide equal rights between husband and wife.